ANALISIS MAKNA METAFORA KATA USHI ‘SAPI’ KAJIAN SEMANTIK KOGNITIF - Sari S, Yuli Purnama; Aibonotika, Arza; Isnaini, Zuli Laili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The study described the meaning of metaphor of ushi ‘cow’ in cognitive semantic approach. The pupose of this study is to explains the meaning of ushi that used in Japanese proverbs. Descriptive qualitative reserch with intralingual method is applied to this research. The data collected from online dictionaries, journal, and books related to proverbs that contain the word ushi ‘cow’. It has been found that the cow is used to imaged things that are big, stupid, simple, slow and stratified society from the lower class.Key word : Semantic cognitive, metaphor, ushi ‘cow’